Epsilon wave: A review of historical aspects - Andrés Ricardo Pérez-Riera; Raimundo Barbosa-Barros; Rodrigo Daminello-Raimundo; Luiz Carlos de Abreu; Javier García-Niebla; Mauro José de Deus Morais; Kjell Nikus; Frank I. Marcus (Indian Pacing and Electrophysiology Journal, 2019)
The epsilon wave of the electrocardiogram (ECG) together with fragmented QRS (fQRS), the terminal conduction delay, incomplete right bundle branch block (IRBBB) and complete/advanced RBBB (CRBBB) of peripheral origin are part of a spectrum of ventricular depolarization abnormalities of arrhythmogenic cardiomyopathy (AC). Although the epsilon wave is considered a major diagnostic criterion for AC since 2010 (AC Task Force Criteria), its diagnostic value is limited because it is a sign of the later stage of the disease. It would be more appropriate to say that the epsilon wave is a “hallmark” of AC, but is of low diagnostic sensitivity. Although the epsilon wave has high specificity for AC, it can be present in other pathological conditions. In this update we will cover the nomenclature, association with disease states and electrocardiographic aspects of the epsilon wave. Keywords: Epsilon wave, Ventricular post-excitation wave, Fontaine wave